Precautionary Savings in Mexico: Evidence From the Mexican Health and Aging Study (2016)
Precautionary saving is the additional saving done by individuals to protect them financially in situations of uncertainty and reduce their vulnerability for negative shocks that may affect their consumption levels. This paper investigates the existence and extent of savings motivated by precaution in Mexico for people aged between 50 and 75, using data from the Mexican Health and Ageing Study 2003. The empirical strategy is based on a test of the direct relationship between the accumulated wealth and the uncertainty generated by the social security status, in particular the availability of health insurance, accounting also for the expectation to receive a retirement pension. The endogeneity-corrected estimates do not yield results that unequivocally support the existence of private savings as a risk protection mechanism, implying that the public protection system has an important role in reducing the vulnerability of the population studied.